Fish larvae distribution among different habitats in coastal East Africa. Issue 1 (11th January 2019) - Hedberg, Per; Rybak, Fanny F.; Gullström, Martin; Jiddawi, Narriman S.; Winder, Monika
Abstract : Fish larvae abundances, diversity and trophic position across shallow seagrass, coral reef and open water habitats were examined to characterize their distribution in coastal East Africa. Larvae were identified to family and analysed for abundance differences between sites and habitats, trophic level using stable‐isotope analysis and parental spawning mode. Abundances differed greatly between sites with the highest numbers of larvae occurring in the open‐water and seagrass habitats. Larval fish diversity was high across habitats with 51 families identified with small differences between sites and among habitats. Notably, larvae of abundant large herbivorous fishes present in reef and seagrass habitats were almost completely absent at all sampling locations. In the seagrass, demersal spawned larvae were more abundant compared with the reef and open‐water habitats. Stable‐isotope analysis revealed that fish larvae have a varied diet, occupying trophic level two to three and utilizing planktonic prey. This study offers new insights into distributional aspects of fish larvae along the East African coast where such information is sparse.